Chronic contained rupture of abdominal aortic aneurysm that developed from chronic abdominal aortic dissection - Shogo Oyama, MD; Shingo Ohuchi, PhD, MD; Takeshi Arai, MD; Yukinobu Ito, PhD, MD (Journal of Vascular Surgery Cases and Innovative Techniques, 2021)
A chronic contained rupture is an extremely rare subtype of abdominal aortic aneurysm rupture. We report the case of a 59-year-old man with a medical history of traumatic lumber fracture 7 years ago. He presented to us with an asymptomatic irregular abdominal aortic aneurysm, and surgery was performed 1 week after he was hospitalized. Based on the medical history, imaging, blood tests, and pathologic results, we determined that the chronic contained rupture progressed from a localized abdominal aortic dissection. This case illustrates the need to follow the morphology of aortic aneurysms if chronic abdominal aortic dissection is observed.